Effects of variety and origin on the metabolic and texture characteristics of quinoa seeds based on ultrahigh-performance liquid chromatography coupled with high-field quadrupole-orbitrap high-resolution mass spectrometry. (December 2022) - Feng, Yuchao; Fan, Xia; Zhang, Shu; Wu, Tong; Bai, Lu; Wang, Haoyu; Ma, Yantao; Guan, Xin; Wang, Changyuan; Yang, Hongzhi
Graphical abstract: Highlights: Varieties and origins had a significant impact on the metabolic characteristics of quinoa and were closely related to lipid, polyphenol, and amino acid substances. When the degree of boiling was the same, the texture properties of white and red quinoa were better than those of black quinoa. The differences in the contents of quercetin, kaempferol and its derivatives, elaidic acid, linoleic acid, prostaglandin, glutathione, 5-aminovaleric acid, etc., among quinoa varieties and origins was extremely significant. The effects of varieties on lipids were greater than those on polyphenol and amino acid substances. Abstract: The nutrition and functionality of Chenopodium quinoa Willd are closely related to its components; however, these properties vary widely in different varieties of C. quinoa Willd from different origins. Using ultrahigh-performance liquid chromatography coupled with high-field quadrupole-orbitrap high-resolution mass spectrometry (UHPLC-QE HF HRMS) for metabolomics analysis, we performed nontargeted metabolomics analysis of C. quinoa Willd of different color varieties and origins and evaluated the texture characteristics after cooking. Both the variety and origin significantly affected the metabolic characteristics of C. quinoa Willd. The differences in the composition and texture properties were closely related to the lipid, amino acid, and polyphenol contents. The contents of kaempferol, catechol, myricetin 7-(6′-galloside), tyrosine, prostaglandin I2, and glutathione in white, red, and black quinoa significantly differed, and the variety had a greater effect on the lipid content than on the polyphenol and amino acid contents. At the same processing level, the texture properties of white and red quinoa were better than those of black quinoa. Furthermore, the contents of differential polyphenols and amino acids in Gansu white quinoa were higher than those in quinoa from the other three producing areas. The contents of differential polyphenols and terpenoids in Inner Mongolia white quinoa were relatively low, whereas in Shanxi white quinoa, the contents of differential amino acids were relatively low and those of differential terpenoids were relatively high. The levels of quercetin and its derivatives, kaempferol and its derivatives, 9-HODE, azelaic acid, sebacic acid, elaidic acid, linoleic acid, prostaglandin H2, glutathione, 5-aminovaleric acid, and other compounds significantly differed in quinoa from different origins; thus, these compounds can be used as metabolic markers to identify the origin of quinoa. The texture properties of white quinoa from Qinghai and Inner Mongolia were better than those of white quinoa from Gansu and Shanxi. Although C. quinoa Willd can tolerate harsh environments, its grain quality varies widely. Cultivating C. quinoa Willd varieties according to local conditions is important for improving their yield and quality.